2016
DOI: 10.1016/j.aap.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a community-based pedestrian injury prevention program on driver yielding behavior at marked crosswalks

Abstract: TitleEffect of a community-based pedestrian injury prevention program on driver yielding behavior at marked crosswalks a b s t r a c tBackground: Few studies have comprehensively evaluated the effectiveness of multi-faceted interventions intended to improve pedestrian safety. "Watch for Me NC" is a multi-faceted, community-based pedestrian safety program that includes widespread media and public engagement in combination with enhanced law enforcement activities (i.e., police outreach and targeted pedestrian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, in the case of taking actions in the educational policy, it is more related to the drivers' behavior when approaching places frequented by pedestrians. The estimated effects of enforcement by drivers yielding to pedestrians in crosswalks are shown by Sandt et al [88,89]. According to Pichayapan et al [90], sometimes reducing the number of road accidents in these places may be the result of minor modernization, such as crosswalk repainting, installing additional lighting to improve visibility, or the use of speed bumps, and additional information signs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of taking actions in the educational policy, it is more related to the drivers' behavior when approaching places frequented by pedestrians. The estimated effects of enforcement by drivers yielding to pedestrians in crosswalks are shown by Sandt et al [88,89]. According to Pichayapan et al [90], sometimes reducing the number of road accidents in these places may be the result of minor modernization, such as crosswalk repainting, installing additional lighting to improve visibility, or the use of speed bumps, and additional information signs.…”
Section: Discussionmentioning
confidence: 99%
“…Vision Zero is a collaborative initiative to eliminate roadway deaths and injuries in North Carolina [24]. The pedestrian-focused initiative Watch For Me NC uses public education and community engagement to reduce pedes- trian and bicycle crashes and appears to positively influence driver behavior [25,26]. Finally, WalkSmartNC is a study focusing on crowd-sourcing pedestrian safety information in downtown Raleigh [27].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, low driver yielding rates were observed at non-signalized marked crosswalks at mid-blocks and near junctions [22][23][24]. The effect of pedestrians' gestures, smile, advance yield markings, and low-cost engineering improvements on driver yielding behavior at marked crosswalks was studied by Zhuang and Wu [22], Guéguen et al [23], Samuel et al [24], and Sandt et al [25] respectively. In case of low driver yielding rates, pedestrians must use their own judgment when they cross the road.…”
Section: Literature Reviewmentioning
confidence: 98%